Propuesta de mejora en una empresa agroindustrial - Pinto Guillén, Alejandro (2020)
The purpose of this project is to propose a proposal for improvement in the process of producing table olives in the company "La Sureñita", firstly conducting a diagnosis of the process to determine the main causes of the problems and subsequently proposing economic solutions, social and viable techniques. To begin, the lack of production planning and control is addressed where the line balancing method is applied to calculate the optimal number of stations (5) and workers (7). Then, using a process activity diagram, the distance traveled by the operators in the process flow is calculated, which is approximately 51.5 meters and a plant redistribution is proposed, adjusting the process in a “U” shape, reducing the distance traveled by the operators at 23 meters and, consequently, the processing time of the products. Lastly, a table of raw material requirements planning is prepared, which, based on the demand for the products, allows calculating the “reorder” point of the types of olives most used in the company. To indicate the optimal quantity to order, the “economic order batch” is calculated. Another important point is the lack of quality control, part in which, after a statistical sampling control and identifying the assignable causes of the defects, a sampling plan was proposed, in addition through a quality characterization matrix, it will achieve indicate to the operators the parameters that they must follow when making a product. Finally, the cost of investment in the project is S /. 9,670, determining by means of an economic analysis the profitability of the project, where the NPV turns out to be 1,363.01 soles, the IRR of 22% and the benefit / cost of 1.14.